2016
DOI: 10.22161/ijeab/1.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Fungal Contamination of Air conditioners filters and Carpets

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Thus, important factors that can modify bioaerosol concentrations inside a bus, as for the chemical pollutants, is the ventilation type and air-conditioning (AC) system (Sowiak et al 2018). Thus, previous studies inside households, university rooms, cars and other indoor spaces, have probed that the use of AC systems when not well designed or maintained can become an additional source of fungal aerosols introduced into indoor air (Hamada and Fujita 2002;Almoffarreh et al 2016). It was shown that during the first 10 min of AC powered on fungal concentrations were highest (Hamada and Fujita 2002;Jo and Lee 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, important factors that can modify bioaerosol concentrations inside a bus, as for the chemical pollutants, is the ventilation type and air-conditioning (AC) system (Sowiak et al 2018). Thus, previous studies inside households, university rooms, cars and other indoor spaces, have probed that the use of AC systems when not well designed or maintained can become an additional source of fungal aerosols introduced into indoor air (Hamada and Fujita 2002;Almoffarreh et al 2016). It was shown that during the first 10 min of AC powered on fungal concentrations were highest (Hamada and Fujita 2002;Jo and Lee 2008).…”
Section: Introductionmentioning
confidence: 99%